"Our Ro gave us so much life and is gone from us". A view of a 'cuarteto' singer through the eyes of his fans. (Revista Argentina de Musicología, 2018)
An attempt to approach the identification process that operates in fans, focusing on the events that followed the death in a car crash of Rodrigo, singer and composer of 'cuarteto' music and the massive impact it had at a mass level. Data was collected on the consuming habits of youngsters and teenagers from the Buenos Aires area, with special emphasis on the music, and the construction of images and representations in order to throw light on the feedback loops and incidence they have on the "musical" choices of the subjects. The purpose is to isolate the factors bearing on the process of identification with the singer.